Comparison on effects of platelet-rich plasma versus autologous conditioned serum on Achilles tendon healing in a rat model - Genç, Erdinç (Acta Orthop Traumatol Turc, 2020)
OBJECTIVE: The aim of this study was to compare the effects of local administrations of platelet-rich plasma (PRP) with autologous conditioned serum (ACS) on Achilles tendon healing in a rat model. METHODS: In this study, 40 male Sprague-Dawley rats, aged 12 months and weighing 350 to 400 g were used. The rats were divided into three groups (n=10 in each group): a control group and two treatment groups (PRP vs ACS). A standardized procedure was applied for the complete rupture and repair of the Achilles tendon in each group. The PRP group received one dose of PRP on the operative area, and ACS group received ACS at 24, 48, and 72 hours after the surgery. The control group received no injection. Animals were sacrificed 30 days after the operation, and tendon healing in each group was assessed histopathologically based on Bonar’s semi-quantitative score and Movin’s semi-quantitative grading scale. For the biomechanical analyses, unoperated Achilles tendons of all rats in the control and ACS groups were also harvested, and pulling tests were applied to the specimen to measure the longitudinal axis strength. The highest force value among the data obtained was defined as the maximum strength value (Fmax). RESULTS: The mean Bonar’s score was significantly lower in the PRP group (3.8±0.8) than in the ACS (4.8±0.45) and control groups (5.2±0.837) (p=0.0028). The mean Movin’s score was significantly lower in the PRP group (7.80±1.49) than in the ACS (9.8±1) and control groups (11.2±2.4) (p=0.029). The ratio of type I collagen was significantly higher in the PRP group (60±6) than in the ACS (52±4.5) and control groups (42±9) (p=0.005). Biomechanical results obtained from operated sites were comparable in terms of Fmax among groups (PRP, 33.93±2.61; ACS, 35.24±3.26; control, 35.69±3.62) (p=0.674). Similarly, the results obtained from unoperated sites were comparable among groups (PRP, 47.71±1.21; ACS, 48.14±2; control, 49.14.69±1.88) (p=0.395). CONCLUSION: In terms of histopathological results, PRP seems to be more effective than ACS for Achilles tendon healing in rats.